1H-nuclear magnetic resonance metabolomics revealing the intrinsic relationships between neurochemical alterations and neurobehavioral and neuropathological abnormalities in rats exposed to tris(2-chloroethyl)phosphate. (June 2018) - Yang, Weiqun; Zhao, Fei; Fang, Yanjun; Li, Li; Li, Chaonan; Ta, Na
Abstract: Tris(2-chloroethyl)phosphate (TCEP) is a widely used environmental organic pollutant. Studies have revealed the presence of both TCEP and its metabolites in environmental media. The neurotoxicity of TCEP has been investigated in vitro but rarely in mammals. This study aimed to determine the neurotoxic effects of TCEP on rats and to explore the possible intrinsic relationships between neurochemical alterations and the neurotoxic effects. For this, 6-week-old female SD rats were administered 50, 100, or 250 mg/kg/d TCEP daily by oral gavage for 60 days. TCEP exposure produced neurotoxicity in the female SD rats. The Morris water maze results revealed a dose-dependent decline in spatial learning and memory functions of exposed rats. In addition, pathological examination of the brain showed apoptotic and necrotic lesions in the CA1 field pyramidal cells of the hippocampus; further, rats treated with the highest TCEP dose showed inflammatory cells and calcified/ossified foci in the cortex areas. Furthermore, 1 H-nuclear magnetic resonance metabolomics results revealed that TCEP exposure interfered with normal biological processes, including amino acid and neurotransmitter metabolism, energy metabolism, and cell membrane function integrity by changing the concentrations of glutamate, γ-aminobutyric acid, N -acetyl-d-aspartate, creatine, and lactic acid metabolites in the brain of treated rats. However, the changes in the concentrations of taurine, myo-inositol, creatine, and choline metabolites, which are associated with antioxidant physiological processes, might be a neuroprotective mechanism to prevent the neurotoxicity induced by TCEP. Thus, metabolomics combined with neuropathology and neurobehavioral analyses provided critical insights to investigate the TCEP-induced neurotoxic effects and mechanisms. Graphical abstract: Highlights: Tris(2-chloroethyl)phosphate is a widely used environmental organic pollutant. Neurotoxicity of TCEP has been investigated in vitro but rarely in mammals. Female SD rats were orally administered different doses of TCEP daily for 60 days. TCEP can interfere with normal physiological and biochemical processes. Metabolomics analysis revealed the TCEP-induced neurotoxic effects and mechanisms.